Overview of the Mars Science Laboratory mission: Bradbury Landing to Yellowknife Bay and beyond. Issue 6 (5th June 2014) - Vasavada, A. R.; Grotzinger, J. P.; Arvidson, R. E.; Calef, F. J.; Crisp, J. A.; Gupta, S.; Hurowitz, J.; Mangold, N.; Maurice, S.; Schmidt, M. E.; Wiens, R. C.; Williams, R. M. E.; et al.
Abstract: The Mars Science Laboratory mission reached Bradbury Landing in August 2012. In its first 500 sols, the rover Curiosity was commissioned and began its investigation of the habitability of past and present environments within Gale Crater. Curiosity traversed eastward toward Glenelg, investigating a boulder with a highly alkaline basaltic composition, encountering numerous exposures of outcropping pebble conglomerate, and sampling aeolian sediment at Rocknest and lacustrine mudstones at Yellowknife Bay. On sol 324, the mission turned its focus southwest, beginning a year‐long journey to the lower reaches of Mt. Sharp, with brief stops at the Darwin and Cooperstown waypoints. The unprecedented complexity of the rover and payload systems posed challenges to science operations, as did a number of anomalies. Operational processes were revised to include additional opportunities for advance planning by the science and engineering teams. Key Points: Curiosity has investigated the habitability of Gale Crater, Mars Curiosity has explored environments with evidence of ancient fluvial activity The unprecedented complexity of the rover challenged science operations